Pengaruh Konseling Islami Terhadap Peningkatan Religiositas Siswa - Sri Rahmadhani; Alfin Siregar (Sekolah Tinggi Agama Islam Sumatera Medan, 2023)
There are many things that affect student religiosity, one of which is counseling services. Counseling services that are not islamically oriented do not necessarily have an impact on increasing religiosity. Therefore this study aims to determine the effect of Islamic counseling in increasing student religiosity. The research method used is a quasi-experimental nonequivalent control group design. The experimental group was given treatment in the form of 6 Islamic counseling sessions which were held once a day. While the control group was not given treatment. The population in the study, class VIII students at MTS Nur Ibrahimy Rantauprapat. The sampling technique used is non-probability sampling with purposive sampling. A sample of 20 people with a reliability score is in the low category. Statistical data analysis techniques were carried out using descriptive statistics. The results of hypothesis testing show that the Asymp. Sig is 0.005, which means that through the results of these calculations it is concluded that the reliability of students sig <0.05 means that the increase in the reliability of class VIII students of MTS Nur Ibrahimy Rantauprapat in the treatment group is higher than the control group. The implication of the research results is to help improve the reliability of class VIII students of MTS Nur Ibrahimy Rantauprapat. Therefore, the dynamics of Islamic counseling groups can facilitate students to increase student religiosity in depth